Arbitration as a Dispute Resolution Mechanism Supporting the Sustainable Development Goals in Private Higher Education - Muntazhor, Ahmad Widad; Mangkudilaga, Bia; Putri, Alya Dean; Rivaldo, Muhammad Reza (Jurnal Ilmu Hukum Kyadiren, 2026)
Private Higher Education Institutions (PTS) in Indonesia are private legal entities with full legal capacity to enter into agreements with third parties, acquire rights, assume obligations, and engage in contractual relations. In its various academic and non-academic activities supporting the Tri Dharma, civil disputes are inevitable. Litigation before the court is still commonly used, yet the judicial process is time-consuming, costly, formalistic, and publicly open to scrutiny—potentially harming institutional reputation. Arbitration emerges as an alternative dispute resolution mechanism that is normatively recognized within Indonesian law, produces final and binding awards, and provides a dispute settlement model that is faster, confidential, flexible, and more compatible with contemporary business needs. This article examines the strategic use of arbitration by PTS as an instrument of good university governance and legal risk management. A clear arbitration clause prevents forum shopping and jurisdictional conflicts before disputes escalate further. Consequently, arbitration should not merely be treated as an optional clause within contracts, but as a deliberate institutional policy to ensure legal certainty, efficiency, and the preservation of institutional credibility